The assessment of forensic molecular markers for skin colour in South Africans - Vanmali, Akshay (Department of Clinical Laboratory Sciences, 2021)
The scientific development of innovative molecular techniques has transformed the approach towards human identification. In forensic casework, the emergence of molecular phenotyping, or phenotypic prediction from DNA, has mitigated some challenges involving the unavailability of references samples for traditional forensic DNA analysis. Molecular phenotyping via SNP analysis can be used as a tool in a forensic setting to predict physical traits, such as hair, skin and eye colour, and provide investigative leads. Several ancestry informative markers (AIMs) have previously been associated with human skin colour in mainly the European and North American population groups, while admixed populations are hardly studied. The present study aims to contribute towards this gap by investigating the relationship between two AIMs (SLC45A2, rs16891982 and SLC24A5, rs1426654) that are typically involved in molecular phenotyping, and melanin index (MI) in the South African (SA) metapopulation (n = 389). The self-reported ancestry, ethnicity and relevant biographic information for each participant was documented and MI was recorded using a dermaspectrophotometer. DNA was extracted from saliva samples and PCR amplification of target regions was performed. Thereafter, SNaPshot® PCR was used to genotype the variants. Significant differences (p < 0.0001) were observed between MI readings and ancestral as well as population census groups. A generalised linear model (GLM) was developed which could accurately predicted the MI readings for each genotype combination within the 95 % confidence interval of the recorded MI readings. Our results suggest that these two markers were consistently associated with MI in the admixed SA population and are thus informative to predict MI in a forensic setting. Finally, this was the first study in a SA context to use SNP analysis for objective MI prediction.